Breastfeeding and Delivery Room Neonatal Collapse. (May 2015) - Friedman, Frederick; Adrouche-Amrani, Lynda; Holzman, Ian R.
Sudden unexpected neonatal collapse in the delivery room is a rare occurrence in healthy term infants. Upper airway obstruction may occur from improper positioning of the newborn even while breastfeeding. Such occlusion may have dire consequences if not recognized immediately. We report 2 healthy term neonates who suffered respiratory arrest while in the mother's arms and attempting breastfeeding. In each case, rapid response by the delivery room nurse averted tragedy. Metabolic and infectious evaluations were unremarkable. Both babies have been well on subsequent examinations. We conclude that proper education of mothers and safe positioning of neonates is critical during the initiation of breastfeeding.